AN ANALYSIS OF GENDER REPRESENTATION IN VISUAL IMAGES IN CHAPTER 1 OF ENGLISH FOR NUSANTARA FOR GRADE 4 STUDENTS - ⁠Azmi Nabilah; Nurus Tsaniatussalamah; Yusmar Amalia Solekha; Adisty Naila Izzati; Sabriena Dhea Azzahra; Mayang Sandyo Anggoro (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines gender representation in visual images in Chapter 1 of English for Nusantara for Grade 4 students. The aim of this study is to analyze how male and female characters are portrayed in terms of roles, activities, and interactions. A qualitative research design was applied using content analysis to interpret the visual data. The data were collected from selected images on pages 1, 3, 8, 13, and 16–17, which show daily routines and family interactions. The findings indicate that both male and female characters are present in the textbook, but their roles are not ,equally distributed. Female characters are more often associated with domestic and caregiving roles, while male characters are portrayed as independent and sometimes dominant. Some images show a more balanced representation, especially in neutral activities, but this pattern does not appear consistently across the chapter. The study shows that gender representation in the visual images still reflects traditional stereotypes and has not fully supported equal representation